Is there a role for salvage re-irradiation in pediatric patients with locoregional recurrent rhabdomyosarcoma? Clinical outcomes from a multi-institutional cohort. Issue 3 (December 2018) - Wakefield, Daniel V.; Eaton, Bree R.; Dove, Austin P.H.; Hsu, Chih-Yang; Merchant, Thomas E.; Pappo, Alberto; Davidoff, Andrew M.; Esiashvili, Natia; Krasin, Matthew J.; Lucas, John T.
Abstract: Background and purpose: Limited data exist detailing the role of salvage reirradiation following local-regional recurrence (LR) in previously irradiated pediatric patients with rhabdomyosarcoma (RMS). Materials and methods: We evaluated outcomes and prognostic factors in a multi-institutional cohort of 23 patients with LR-only ( N  = 19) or LR with distant failure ( N  = 4) RMS managed with ( N  = 12) or without ( N  = 11) re-irradiation who were treated from 1996 to 2012. Results: At a median follow-up of 4.6 years from LR, 7 (30%) patients were alive and 5 (22%) had no evidence of disease. Median OS and PFS from LR were 19.3 and 16.9 months, respectively. LFFS and DFFS at 3 years from relapse were 54% and 56%, respectively. Salvage re-irradiation occurred in 12 (52%) patients, with 9 (75%) receiving resection before re-irradiation. Patients classified as low-risk at diagnosis with favorable primary tumor location had improved 3-year PFS 80% (95% CI 51.6–100%) vs. 47.1% (95% CI 27.3–81.2%), p  = 0.066], and OS 80% [(95% CI 22.4–100%) vs. 47.1% (95% CI 27.3–81.3%), p  = 0.051] following LR. Median LFFS and OS in unirradiated vs. re-irradiated patients was 12.4 vs. 19.6 ( p  = 0.1) and 18.8 vs. 26.1 months ( p  = 0.46). No patients experienced ≥grade 4 acute toxicity from re-irradiation. LR failure was a component of cancer-related death in 60% vs. 40% of the unirradiated and re-irradiated group ( p  = 0.02). Conclusion: Salvage re-irradiation appears tolerable with acceptable morbidity and may reduce the risk of subsequent LR as a component of death in patients with LR RMS.